2016
DOI: 10.3109/10428194.2016.1157868
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics ofBCR-ABLkinase domain mutations in chronic myeloid leukemia from India: not just missense mutations but insertions and deletions are also associated with TKI resistance

Abstract: We document the characteristics of BCR-ABL kinase domain mutations (KDM) in the largest study from India comprising of 385 patients and demonstrate that more than half (51.9%) of these patients have detectable abnormalities in the KD both in adult and in pediatric chronic myelogenous leukemia (CML). These comprise singly occurring missense mutations (25.5%), polyclonal/compound point mutations (4.9%), and insertions/deletions (29.6%). Missense mutations were most commonly seen in the imatinib-binding region fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 45 publications
6
23
0
1
Order By: Relevance
“…Our data again demonstrated that the incidence of mutation varies depending on the different populations. Most of cases with imatinib resistance in our study were in chronic phase, which is in line with previous observations [8,11,20]. Of those, 122 cases (86.5%) at chronic phase, 7 cases (5%) at accelerated phase and 12 cases (8.5%) at blast phase.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Our data again demonstrated that the incidence of mutation varies depending on the different populations. Most of cases with imatinib resistance in our study were in chronic phase, which is in line with previous observations [8,11,20]. Of those, 122 cases (86.5%) at chronic phase, 7 cases (5%) at accelerated phase and 12 cases (8.5%) at blast phase.…”
Section: Resultssupporting
confidence: 80%
“…As the national diagnostic and treatment center for CML, we aimed to utilize NGS system (MiSeq sequencer, Illumina, USA) to investigate the occurrence and ratio of kinase domain mutations for a group of our CML patients in Vietnam. The results could add some more information to previous serial studies of kinase domain mutation of CML [8,11].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In 2016, a group of Indian researchers6 conducted a large screening study (385 resistant patients) that revealed a statistically significant relationship between deletion and TKI resistance. Our screening study showed that the deletion is detected approximately equally in sensitive and TKI‐resistant patients (47% and 53%, respectively); this fact is consistent with the alternative splicing theory.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно исследованиям, проведенным в раз-личных странах, спектр мутаций, частота обнаружения и доля ассоциированной с мутациями устойчивости оказываются примерно одинаковыми [4][5][6][7][8]. Наиболее часто встречающимися мутациями гена BCR-ABL (суммарно 85 %), связанными с резистентностью к иматинибу, являются семь: M244V, G250E, Y253F/H, E255K/V, T315I, M351T и F359V.…”
Section: полученоunclassified